Big data analytics and intelligence: A perspective for health care - Muruganantham A.; Nguyen P.T.; Lydia E.L.; Shankar K.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The term big data refers to a group of large and vast amount of data collected from many research organizations, hospitals and scientific organizations which can be available for the healthcare. Such big data have potential for improving in the research in healthcare. The big data helps to analyze the clinical datasets and provides the key insights for the patients care. Such data can be analyzed by several multidisciplinary methods. The big data and intelligence model also helps to provide support in taking recommend action and make the decision making model more strong. The Healthcare medical artificial intelligence system mainly uses a computer software to perform the health and clinical diagnoses and suggest the proper treatments. Predictive analysis is also the most important part of Big Data Analytics which use datasets and historical data to make the predictions about the disease. But such predictions results may vary for person to person. Every person have different immunity power, so an detailed research may help to lead better results. There are many techniques and algorithms are available such as PPDM, Machine Learning, Data Mining Algorithms, Artificial Intelligence etc. In this research it is studied that how health care data can helps patients in predicting diseases and improve the treatment. BEIESP.